2023
DOI: 10.1186/s12889-023-15292-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of national health insurance membership among the poor with different education levels in Indonesia

Abstract: Background Indonesia has made significant progress in expanding universal health coverage (UHC) through its National Health Insurance (NHI) mechanism. However, in the context of NHI implementation in Indonesia, socioeconomic disparities caused its subpopulations to have different literacy of NHI concepts and procedures, increasing the risk of healthcare access inequities. Hence, the study aimed to analyse the predictors of NHI membership among the poor with different education levels in Indones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“… 6 The reason is uncertain income, considering that most lower-middle-class people work in the informal sector. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 The reason is uncertain income, considering that most lower-middle-class people work in the informal sector. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…The program aims to fulfill the basic needs of the community in the health sector to protect the community. 8 In this program, all people are required to become NHI participants. By participating, it is hoped that the community will be protected and get health service guarantees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The study found that the educational attainment of the poor in uences the decision to become members of the National Insurance Scheme than those with less or no education. 7 In order to control and improve the e ciency of insurers' data management, a uni ed information system in healthcare organizations is important, which should expand cooperation with the medical industry to further develop the application processes of big healthcare data and eliminate privacy risks. 8 There are problems in the CIS countries that hinder the coverage of the population with compulsory health insurance.…”
Section: Introductionmentioning
confidence: 99%
“…(Febriyanti et al, 2023) In Indonesia, despite setting a goal of 95% membership coverage by the end of 2019, NHI only managed to reach 85.3%. (Putri et al, 2023) However, in practice, health services in hospitals often become a public issue because of the perceived differences they receive, which can impact patient satisfaction. Since the public still sees the system favorably, interest in NHI services is typically minimal.…”
Section: Introductionmentioning
confidence: 99%